Screening and Evaluation of New Hydroxymethylfurfural Oxidases for Furandicarboxylic Acid Production - Viñambres, Mario; Espada, Marta; Martínez, Angel T.; Serrano, Ana (Applied and environmental microbiology, 2020)
HMFO is the only enzyme described to date that can catalyze by itself the three consecutive oxidation steps to produce FDCA from HMF. Unfortunately, only one HMFO enzyme is currently available for biotechnological application. This availability is enlarged here by the identification, heterologous production, purification, and characterization of two new HMFOs, one from Pseudomonas nitroreducens and one from an unidentified Pseudomonas species. Compared to the previously known Methylovorus HMFO, the new enzyme from P. nitroreducens exhibits better performance for FDCA production in wider pH and temperature ranges, with higher tolerance for the hydrogen peroxide formed, longer half-life during oxidation, and higher yield and total turnover numbers in long-term conversions under optimized conditions. All these features are relevant properties for the industrial production of FDCA. In summary, gene screening and heterologous expression can facilitate the selection and improvement of HMFO enzymes as biocatalysts for the enzymatic synthesis of renewable building blocks in the production of bioplastics. The enzymatic production of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF) has gained interest in recent years, as FDCA is a renewable precursor of poly(ethylene-2,5-furandicarboxylate) (PEF). 5-Hydroxymethylfurfural oxidases (HMFOs) form a flavoenzyme family with genes annotated in a dozen bacterial species but only one enzyme purified and characterized to date (after heterologous expression of a Methylovorus sp. HMFO gene). This oxidase acts on both furfuryl alcohols and aldehydes and, therefore, is able to catalyze the conversion of HMF into FDCA through 2,5-diformylfuran (DFF) and 2,5-formylfurancarboxylic acid (FFCA), with only the need of oxygen as a cosubstrate. To enlarge the repertoire of HMFO enzymes available, genetic databases were screened for putative HMFO genes, followed by heterologous expression in Escherichia coli . After unsuccessful trials with other bacterial HMFO genes, HMFOs from two Pseudomonas species were produced as active soluble enzymes, purified, and characterized. The Methylovorus sp. enzyme was also produced and purified in parallel for comparison. Enzyme stability against temperature, pH, and hydrogen peroxide, three key aspects for application, were evaluated (together with optimal conditions for activity), revealing differences between the three HMFOs. Also, the kinetic parameters for HMF, DFF, and FFCA oxidation were determined, the new HMFOs having higher efficiencies for the oxidation of FFCA, which constitutes the bottleneck in the enzymatic route for FDCA production. These results were used to set up the best conditions for FDCA production by each enzyme, attaining a compromise between optimal activity and half-life under different conditions of operation. IMPORTANCE HMFO is the only enzyme described to date that can catalyze by itself the three consecutive oxidation steps to produce FDCA from HMF. Unfortunately, only one HMFO enzyme is currently available for biotechnological application. This availability is enlarged here by the identification, heterologous production, purification, and characterization of two new HMFOs, one from Pseudomonas nitroreducens and one from an unidentified Pseudomonas species. Compared to the previously known Methylovorus HMFO, the new enzyme from P. nitroreducens exhibits better performance for FDCA production in wider pH and temperature ranges, with higher tolerance for the hydrogen peroxide formed, longer half-life during oxidation, and higher yield and total turnover numbers in long-term conversions under optimized conditions. All these features are relevant properties for the industrial production of FDCA. In summary, gene screening and heterologous expression can facilitate the selection and improvement of HMFO enzymes as biocatalysts for the enzymatic synthesis of renewable building blocks in the production of bioplastics.